2012
DOI: 10.1016/j.jalgebra.2012.07.054
|View full text |Cite
|
Sign up to set email alerts
|

Hyperelliptic curves and their invariants: Geometric, arithmetic and algorithmic aspects

Abstract: We apply classical invariant theory of binary forms to explicitly characterize isomorphism classes of hyperelliptic curves of small genus and, conversely, propose algorithms for reconstructing hyperelliptic models from given invariants. We focus on genus 3 hyperelliptic curves. Both geometric and arithmetic aspects are considered. 4. Field of definition 32 4.1. Field of definition and field of moduli: general facts 32 4.2. The hyperelliptic case 33 4.3. The hyperelliptic case with no extra-automorphism 35 4.4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(95 citation statements)
references
References 38 publications
(39 reference statements)
3
92
0
Order By: Relevance
“…. , J 7 ) = 0 is the zero polynomial), but J 8 , J 9 , J 10 are subject to algebraic relations involving the first six invariants and known as syzygies, see [35,25].…”
Section: Integrity Basismentioning
confidence: 99%
“…. , J 7 ) = 0 is the zero polynomial), but J 8 , J 9 , J 10 are subject to algebraic relations involving the first six invariants and known as syzygies, see [35,25].…”
Section: Integrity Basismentioning
confidence: 99%
“…In [19], the authors showed that these invariants are also generators of the algebra of invariants and determine hyperelliptic curves of genus 3 up to isomorphism in characteristic p > 7. Later, in his thesis [3], Basson provided some extra invariants that together with the classical Shioda invariants classify hyperelliptic curves of genus 3 up to isomorphism in characteristics 3 and 7.…”
Section: Shioda Invariantsmentioning
confidence: 99%
“…We recall that the discriminant ∆ of a hyperelliptic curve C of genus 3 is an invariant of degree 14 (Section 1.5 of [19]). For our computations, we considered the following absolute 3 invariants, derived using the Shioda invariants: The numerical data in Table 5.1 shows the tight connection between the odd primes appearing in the denominators of these invariants, the odd primes of bad reduction for the hyperelliptic curve, and the odd primes dividing the denominators of j 1 , j 2 and j 3 .…”
Section: 1mentioning
confidence: 99%
“…Now there is a notion of a normalized representative of such a point [16]. We call a polynomial π normalized if its tuple of coefficients is normalized.…”
Section: Proposition 47 With the Above Notation Let X Be A Curve Ovmentioning
confidence: 99%
“…So there exists a finite subset I of this set with this property as well. Let c I = (c i ) i∈I be the corresponding point in the projective space weighted by its indices, and choose a normalized representative c I,0 of c I [16]. There exists a scaling t → αt of t that transforms c I into c I,0 , which is uniquely determined up to a power of the automorphism t → ζ n t since the elements in I generate Z.…”
Section: Remark 57mentioning
confidence: 99%